Strategi Guru Mengelola Kelas dalam Pembelajaran Anak Usia Dini di TK Kristen Generasi Ungul Bajawa - TURE, YASINTA; WEA, LUDGARDIS; ENE, MARIA ASRI; FONO, YASINTA MARIA (PT Rizkarya Cendekia Pustaka, 2026)
Teachers are managers or administrators who play a role in creating a conducive classroom for students. Early childhood education (PAUD) is a crucial early stage in forming the foundation for children's intellectual, emotional, social, and spiritual development. The purpose of this study was to determine the strategies teachers employ in managing the classroom at the Generasi Ungul Christian Kindergarten in Bajawa. The method used in this study was a descriptive qualitative research method. The subjects were teachers at the Generasi Ungul Christian Kindergarten in Bajawa. The results showed that teachers' strategies in managing the classroom at the Generasi Ungul Christian Kindergarten in Bajawa include creating a safe classroom environment free of objects that could harm children. They also established simple and positive classroom rules, such as neatness, raising their hands before speaking, sharing, and involving children in creating rules to foster a sense of ownership. These strategies are considered effective in creating a safe and comfortable learning environment that supports the social and emotional development of early childhood.